A Competitive Model of Lenggong Valley as a Rural Heritage Destination in Malaysia - Abdul Aziz, Nur Izwani; Jaafar, Mastura; Hassan, Fatimah; J. Kadi, Alaa (EDP Sciences, 2014)
Besides rural attraction, Lenggong Valley has been acknowledged as an important archeological attraction in the state of Perak. On 30th June 2012, Lenggong Valley has been declared as the world heritage site by UNESCO for its archaeological heritage which includes four excavation sites divided into two clusters. Cluster 1 consists of the Bukit Bunuh-Kota Tampan core zone and its own buffer zone, while Cluster 2 consists of three core zones, namely Bukit Kepala Gajah, Bukit Gua Harimau and Bukit Jawa, all enclosed within a single buffer zone. For Perak, this recognition is important to attract more visitors to Perak this year, in conjunction with the Visit Perak Year 2012. From a tourism perspective, a place competitiveness can be increased by utilizing the unique resources of a particular place. The aim of this paper is to propose the competitiveness model of the Lenggong Valley. Various models on destination competitiveness will be reviewed.